Monetary economics - Dennis, Geoffrey E. J (London : Longman, 1981)
The book provides a simple introduction to the essential issues of monetary economics as they stand at the end of the 1970s. It also highlights some of monetary models adopted at various times by different authors.
includes index
Bibliography p.286-300
usc 31/05/17
Loans
Keywords: Money; Modern economics